Review of Pierre Birnbaum’s A Tale of Ritual Murder in the Age of Louis XIV: The Trial of Raphaël Lévy, 1669 - Plakotos, Giorgos (Historein, 2014)
Pierre Birnbaum, A Tale of Ritual Murder in the Age of Louis XIV: The Trial of Raphaël Lévy, 1669, Stanford: Stanford University Press, 2012. 178 pp, 12 illus.